SENYAPAN DAN KILIR LIDAH DALAM ACARA GELAR WICARA MATA NAJWA 2020 SEBAGAI KAJIAN PSIKOLINGUISTIK - Ali Manshur; Fina Zaidatul Istiqomah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Speaking is one of the four language skills. Speaking skills are always needed in human interaction activities, especially communicating. However, humans in speaking experience often experience mistakes in practice, one of which is the Silent and Tongue Shrink at the Mata Najwa 2020 talk show. On that basis the researcher wants to explore, look for the causes and processes of the occurrence of Silence and Tongue Flashes from several sources in the event. Tongue smiles and flashes are one of the obstacles that occur in communicating activities, both official and non-official. This type of research is descriptive qualitative with research carried out to determine the problem without comparing or linking the existing problems with the interversion picture of research on a phenomenon. In this study, researchers used a data collection technique with a listening method consisting of listening proficiently, listening freely fold proficiently, taking notes, and recording. By using Graunded Theory analysis with the Axial Coding method Paradigm model. Based on the analysis obtained from the results of the research that the Silence and the Flickering of the Tongue in the 2020 Mata Najwa talk show, there are lots of silences performed with various factors that influence it.